The allosteric dopamine D1 receptor potentiator, DETQ, ameliorates subchronic phencyclidine-induced object recognition memory deficits and enhances cortical acetylcholine efflux in male humanized D1 receptor knock-in mice - Meltzer, Herbert Y.; Rajagopal, Lakshmi; Matrisciano, Francesco; Hao, Junliang; Svensson, Kjell A.; Huang, Mei (Behavioural brain research, 2019)
•The D1 receptor PAM DETQ restored NOR in scPCP-treated hD1 knock-in mice.•The efficacy of DETQ on NOR was blocked by the D1R antagonist, SCH391660.•There was no inverted U-shaped dose response curve or tolerance in the NOR test.•Rivastigmine, with or without DETQ, reversed the deficit in NOR.•DETQ enhances ACh efflux in PFC and HIP in saline- but not scPCP-treated hD1 mice. Diminished dopamine D1 stimulation may contribute to cognitive impairment in Alzheimer’s and Parkinson’s diseases, schizophrenia, and other neuropsychiatric disorders. However, orthosteric D1 receptor (D1R) agonists produce receptor desensitization and an inverted U-shaped dose-response curve, but positive allosteric modulators (PAMs) do not. We examined the cognitive effects of DETQ, a D1R PAM, in mice genetically modified to express the human D1 receptor (“hD1 mice”). Phencyclidine (PCP), a noncompetitive N-methyl-D-aspartate receptor antagonist, dosed seven days (subchronic), followed by withdrawal, produced a prolonged deficit in novel object recognition (NOR) memory, which was reversed by acute treatment with DETQ, with no evidence for an inverted U-shaped response. This was blocked by the D1R antagonist, SCH391660. Single doses of D1R agonists, SKF38393 and SKF82958, and the acetylcholinesterase inhibitor, rivastigmine, alone and the combination of subeffective doses of both DETQ and rivastigmine, also restored NOR in both subchronic PCP-treated in hD1 mice. DETQ increased cortical and hippocampal acetylcholine efflux after both acute and subchronic dosing in hD1 mice. Subchronic but not acute DETQ, inhibited glutamate and GABA efflux. DETQ-induced acetylcholine efflux was absent in subchronic PCP-treated mice, indicating that restoration of NOR in subchronic PCP-treated mice does not require cortical acetylcholine efflux. This is additional evidence that DETQ stimulates D1R without producing an inverted-U-shaped response curve and increases neurotransmitter release in the mPFC and HIP without causing tolerance. The ability of D1 PAMs to improve cognition in humans with neuropsychiatric disorders without evidence of tolerance or an inverted-U-shaped response curve needs to be established clinically.